Parasite: A Philosophical Exploration - Stamatellos, Giannis,; Botz-Bornstein, Thorsten, (Value Inquiry Book Series ;, 2022)
Parasite presents the ethico-biological problem of parasitism in a metaphorical and artistic fashion. In this book, philosophers explore the film using sources such as the ancient satirist Lucian's De Parasito, Nietzsche's "the vengeance of the weak," Dostoyevsky's "Underground," or Marxism, among others.